Confirmed rare copy number variants implicate novel genes in schizophrenia. (22nd March 2010) - Tam, Gloria W.C.; van de Lagemaat, Louie N.; Redon, Richard; Strathdee, Karen E.; Croning, Mike D.R.; Malloy, Mary P.; Muir, Walter J.; Pickard, Ben S.; Deary, Ian J.; Blackwood, Douglas H.R.; Carter, Nigel P.; Grant, Seth G.N.
Abstract : Understanding how cognitive processes including learning, memory, decision making and ideation are encoded by the genome is a key question in biology. Identification of sets of genes underlying human mental disorders is a path towards this objective. Schizophrenia is a common disease with cognitive symptoms, high heritability and complex genetics. We have identified genes involved with schizophrenia by measuring differences in DNA copy number across the entire genome in 91 schizophrenia cases and 92 controls in the Scottish population. Our data reproduce rare and common variants observed in public domain data from >3000 schizophrenia cases, confirming known disease loci as well as identifying novel loci. We found copy number variants in PDE10A (phosphodiesterase 10A), CYFIP1 [cytoplasmic FMR1 (Fragile X mental retardation 1)-interacting protein 1], K + channel genes KCNE1 and KCNE2, the Down's syndrome critical region 1 gene RCAN1 (regulator of calcineurin 1), cell-recognition protein CHL1 (cell adhesion molecule with homology with L1CAM), the transcription factor SP4 (specificity protein 4) and histone deacetylase HDAC9, among others (see http://www.genes2cognition.org/SCZ-CNV ). Integrating the function of these many genes into a coherent model of schizophrenia and cognition is a major unanswered challenge.